Alcohol use in young adults associated with cortical gyrification. (1st April 2020) - Hua, Jessica P.Y.; Piasecki, Thomas M.; McDowell, Yoanna E.; Boness, Cassandra L.; Trela, Constantine J.; Merrill, Anne M.; Sher, Kenneth J.; Kerns, John G.
Highlights: Young adulthood is a critical stage in which neural insults are greatly neurotoxic. Cortical gyrification is a marker of underlying neural connectivity. No study has looked at cortical gyrification and alcohol use in young adulthood. Alcohol use in young adults is associated with cortical gyrication. Abstract: Background: Young adulthood has the highest rates of alcohol use and high-risk drinking behavior. This period is also a critical neurodevelopmental stage, with neural insults having a profound neurotoxic effect on the brain. Cortical gyrification is thought, in part, to reflect early brain maturation (e.g., hypogyrification in fetal alcohol syndrome). There is also evidence that cortical gyrification is sensitive to later-life events (e.g., fluctuations in malnutrition in young adults). However, no study has examined how alcohol use in young adulthood is associated with cortical gyrification. Methods: We examined the associations between cortical gyrification with lifetime alcohol use and past year hangover symptoms in young adults ( N = 78). Results: Lifetime alcohol use was associated with hypogyria in multiple cortical regions ( r s ≤ -.27, p s ≤ .0159; right orbitofrontal, right temporal pole, and left lateral occipital). Further, past year hangover symptoms were associated with hypogyria ( r s ≤ -.27, p s ≤ .0034), overlapping with lifetime alcohol use (right orbitofrontal and left lateral occipital). Hangover symptoms were also uniquely associated with hypogyria of other cortical regions ( r s ≤ -.30, p s ≤ .0002; right parahippocampal gyrus, left inferior temporal/parahippocampal gyrus and right anterior insula). Conclusions: Thus, results suggest that young adulthood is a critical period for targeted prevention and intervention, especially for individuals exhibiting heavy alcohol consumption and high-risk drinking behavior.